2021
DOI: 10.53112/tudear.999869
|View full text |Cite
|
Sign up to set email alerts
|

Theology Students’ Views on Distance Learning in The Covid-19 Pandemic Process

Abstract: Covid-19 pandemi sürecinde, İlahiyat fakültesi öğrencilerinin uzaktan eğitime ilişkin görüşleri ve karşılaştıkları problemleri ortaya koymayı amaçlayan bu çalışmada, karma yöntem benimsenmiş olup, yakınsayan paralel desen kullanılmıştır. Araştırma evrenini 2020-2021 öğretim yılı Bahar döneminde Harran Üniversitesi İlahiyat Fakültesi'nde okuyan yaklaşık 1700 öğrenci oluştururken, araştırma örneklemini ise bu grubu temsilen 447 öğrenci oluşturmaktadır. Veri toplama aracı olarak anket kullanılmıştır. Araştırmaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Research has shown that some similar studies have been conducted in parallel with the result of the behavioural problems seen in students during the face-to-face education period (Duan et al, 2020;Marie et al, 2022;Uçkaç, 2020). Furthermore, some other studies have been found in the related literature, in which such similar results as students' lack of computers and tablets have been reported (Aydemir, 2021;Aydın, 2021;Balaman & Hanbay Tiryaki 2021;Çilek et al, 2021;Çok, 2021;Deli, 2021;Demir & Özdaş, 2020;Karaibiş, 2021;Kavuk & Demirtaş, 2021;Laçin, 2021;Morgan, 2020;Noyan, 2022;Özdemir, 2021;Sertkaya Dinler, 2022;Seyhan, 2021;Tanta, 2021;Toraman & Kayalar, 2020;Wössmann, 2020;Uyar, 2020;Yeşilyurt, 2021;Yılmaz et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…Research has shown that some similar studies have been conducted in parallel with the result of the behavioural problems seen in students during the face-to-face education period (Duan et al, 2020;Marie et al, 2022;Uçkaç, 2020). Furthermore, some other studies have been found in the related literature, in which such similar results as students' lack of computers and tablets have been reported (Aydemir, 2021;Aydın, 2021;Balaman & Hanbay Tiryaki 2021;Çilek et al, 2021;Çok, 2021;Deli, 2021;Demir & Özdaş, 2020;Karaibiş, 2021;Kavuk & Demirtaş, 2021;Laçin, 2021;Morgan, 2020;Noyan, 2022;Özdemir, 2021;Sertkaya Dinler, 2022;Seyhan, 2021;Tanta, 2021;Toraman & Kayalar, 2020;Wössmann, 2020;Uyar, 2020;Yeşilyurt, 2021;Yılmaz et al, 2021).…”
Section: Discussionsupporting
confidence: 58%